Data-Driven Insights for Tourism Development in East Java Using Directed Graphs - Galih Pradananta; Badara Shofi Dana (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
This study aims to analyze the tourism network in East Java using Google Trends data and directed graph models. Data were collected based on search queries combining the keyword